2001
DOI: 10.1038/sj.bmt.1703192
|View full text |Cite
|
Sign up to set email alerts
|

Granulomatous pneumonitis following bone marrow transplantation

Abstract: Summary:We describe the rare occurrence of a granulomatous pneumonitis seen in a patient following allogeneic bone marrow transplantation. Interestingly sarcoidosis was diagnosed in the marrow donor less than a year after donating his bone marrow. Bone Marrow Transplantation (2001) 28, 627-630. Keywords: alveolitis; extrinsic allergic; sarcoidosis; bone marrow transplantation; granuloma Case report, recipientA 37-year-old white female presented with a lump in her neck in November 1996. Biopsy revealed a large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
20
1
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 8 publications
1
20
1
5
Order By: Relevance
“…Of interest is that three of the four previously reported patients received stem cells from siblings diagnosed with sarcoidosis. 5,7,8 However, in our patients neither of the donors had any evidence of sarcoidosis, and it is possible that the immune dysregulation following alemtuzumab-based conditioning 10 may have precipitated the development of sarcoidosis.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…Of interest is that three of the four previously reported patients received stem cells from siblings diagnosed with sarcoidosis. 5,7,8 However, in our patients neither of the donors had any evidence of sarcoidosis, and it is possible that the immune dysregulation following alemtuzumab-based conditioning 10 may have precipitated the development of sarcoidosis.…”
mentioning
confidence: 82%
“…6 In contrast, it is rare to encounter sarcoidosis of the liver after HSCT. 5 We know of only four previous cases of patients developing sarcoidosis following allogeneic stem cell transplantation, 5,7-9 and of only one with hepatic sarcoidosis. 7 All previously reported patients received standard conditioning regimens, whereas both our patients underwent RIC-HSCT.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In case-control studies from the Isle of Man, 40% of sarcoidosis cases reported contact with a patient with sarcoidosis before disease onset, compared with only 1% of control subjects (25,26). Finally, some patients developed sarcoidosis after receiving a transplant from a patient with sarcoidosis (27)(28)(29)(30). These observations strongly support the presence of a transmissible agent in sarcoidosis.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] Previous study never referred to chimerism of sarcoidosis lesions. This is the first report in which chimerism of lymph nodes where sarcoidosis had infiltrated was investigated and the first study showing that lymph nodes contained mostly donor-type cells.…”
mentioning
confidence: 99%